Development Of Educational Material For Nutrition And Hypertension - Didit Damayanti; Antonius Sri Hartono; Nils Aria Zulfianto; Mimin Aminah (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
High prevalence of hypertension in Indonesia (25.8%) should be prevented because it affects the onset of disease complications, reduced productivity and increased health care costs. Until now, there has not found the media developed specifically to prevent and treat hypertension. The study aims was developed and assessed the use of nutrition and hypertension media for counseling. The research started with the development of educational media. The study design was post test using nutrition and hypertension media by intervention group compared to the control group using hypertension leaflet. Age, duration of working respondents did not differ significantly (p> 0.05) among 17 respondents from intervention group and 14 respondents from control group. The study showed the score usage of media was 3.16 higher among intervention group than the control group 2.99. However, Mann-Whitney test showed no significant differences (p> 0.05). From fourteen aspects result showed significant scores differences (p <0.05) on the aspects of appearance of image and colors. The used of key pieces of media seemed helpful (52.94% - 76.47%) and very helpful (23.53% - 47.06%) for majority of respondents during counseling. It suggested that educational media of nutrition and hypertension can be reproduce and use in the primary health care.